2010
DOI: 10.1007/s00338-010-0670-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of internal macrobioeroder densities in living massive Porites to turbidity and chlorophyll on the Australian Great Barrier Reef

Abstract: This study investigates the relationship between the density of internal macrobioeroders in living massive Porites and nutrient status. The study was conducted along turbidity and chlorophyll gradients towards river mouths on 12 reefs in four regions of the inshore Great Barrier Reef. Mean internal macrobioeroder densities doubled from 2 to 8 m depth, and at the 8 m sites, densities increased 4-to 7-fold towards the river mouths in all regions. Densities also increased 1.6-fold for each additional 1 NTU turbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 41 publications
3
37
0
Order By: Relevance
“…This indicates that bioerosion is less sensitive to low salinities than coral growth, and that SGD‐derived nutrients likely increase bioerosion rates until nutrients become saturating or conditions become stressful, at which point bioerosion rates plateau. This is consistent with previous studies that have noted increased bioerosion with increasing nutrients (Edinger et al ; Holmes 2000; Le Grand and Fabricius ). Studies that have assessed bioerosion rates in the Hawaiian Archipelago have found the highest bioerosion rates at Kahekili, Maui, a site with a significant influx of nutrient‐rich SGD (Prouty et al ; Silbiger et al ), indicating that the relationship between SGD and bioerosion in the current study is not a localized phenomenon.…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that bioerosion is less sensitive to low salinities than coral growth, and that SGD‐derived nutrients likely increase bioerosion rates until nutrients become saturating or conditions become stressful, at which point bioerosion rates plateau. This is consistent with previous studies that have noted increased bioerosion with increasing nutrients (Edinger et al ; Holmes 2000; Le Grand and Fabricius ). Studies that have assessed bioerosion rates in the Hawaiian Archipelago have found the highest bioerosion rates at Kahekili, Maui, a site with a significant influx of nutrient‐rich SGD (Prouty et al ; Silbiger et al ), indicating that the relationship between SGD and bioerosion in the current study is not a localized phenomenon.…”
Section: Discussionsupporting
confidence: 93%
“…In colonies smaller than the quadrat, the five deepest grooves on the entire colony were measured. -The density of externally visible apertures of macrobioeroders was determined on upward facing surfaces with living tissue (Cooper et al, 2008;LeGrand and Fabricius, 2011). In Study 1, colonies >1 m were sub-sampled in 3 replicate 25 Â 25 cm quadrats, while colonies <1 m in diameter were counted in total after determining their living surface area.…”
Section: Massive Porites Spp Coralsmentioning
confidence: 99%
“…). In several field studies, bioerosion increased in eutrophic relative to oligotrophic conditions (e.g., Le Grand and Fabricius , DeCarlo et al. ), likely due to increased food availability to filter feeding bioeroders.…”
Section: Introductionmentioning
confidence: 99%
“…) and local eutrophication (e.g., Fabricius , Hutchings et al. , Le Grand and Fabricius ). These stressors threaten to shift reefs from a state of net accretion to net erosion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation